Asian Perceptions of Gulf Security - Sim, Li-Chen; Fulton, Jonathan (Changing Dynamics in Asia-Middle East Relations, 2023)
Gulf stability is coming to play a larger role in the foreign policy calculus of many states, but the evolving role of Asian powers is largely under-represented in the International Relations literature. This volume addresses this gap with a set of empirically rich, theory driven case studies written by academics from or based in the countries in question. The underlying assumption is not that Asian powers have already become important security actors in the Gulf, but rather that they perceive the Gulf as a region of increasing strategic relevance. How will leaders in these countries adjust to an evolving regional framework? Will there be coordinated efforts to establish an Asian-centered approach to Gulf stability, or will Asian rivalries make the region a theater of competition? Will US-China tensions force alignment choices among Asian powers? Will Asian states balance, bandwagon, hedge, or adopt some other approach to their Gulf relationships? These questions become even more important as the western boundaries of Asia increasingly come to incorporate the Middle East. The book will appeal to scholars and students in the fields of International Relations, Security Studies, and International Political Economy, as well as area specialists on the Gulf and those working on foreign policy issues on each of the Asian countries included. Professionals in government and non-government agencies will also find it very useful.